Prenatal sex determination in suspicious cases of X-linked recessive diseases by the amelogenin gene - Rahimi, Amir Abbas (Mashhad University of Medical Sciences, 2014)
Objective(s): To determine the fetal discernment in suspected cases of sex linked recessive disease in the first trimester of pregnancy. Materials and Methods: After collection of 100 Chorionic Villi samples, the DNAs were extracted and baby gender was determined. Meanwhile, after increasing the sensitivity, the system was able to detect the sex of each cell which was obtained by biopsy. Results: Early fetal gender of 100 Chorionic Villi samples were assessed by PCR. After increasing sensitivity of the assay, the sexes in 13 fetuses that were in different cellular stages were detected. Morover, sexes were detected in two unfertilized and one fertilized ovum but without any division. Conclusion: Sex detection of fetus before delivery in the first trimester of pregnancy, will prevent babies with abnormalities being born. It can also be used in detection of recessive sex related diseases in In Vitro Fertilization cases for sex detection and to transfer female fetus to the mother. Our optimized molecular detection system was designed on the basis of amelogenin gene, which can determine the sex in blood, chorionic villi, and single cell in vitro fertilization with high sensitivity and specificity.